Safety learning system development—incident reporting component for family practice. Issue 3 (9th June 2010) - O'Beirne, M; Sterling, P; Reid, R; Tink, W; Hohman, S; Norton, P
Abstract : Objective: To determine the required components for developing the reporting components of a safety learning system (SLS) for community-based family practice. Methods: Multiple databases were searched for all languages for all types of papers related to medical safety in community practice: Books@Ovid, BIOSIS Previews, CDSR, ACP Journal Club, DARE, CCTR, Ageline, AMED, CINAHL, EMBASE, HealthSTAR, Ovid MEDLINE In-Process, Other Non-Indexed Citations, Ovid MEDLINE, PsycINFO, HAPI and PsycBOOKS. A grey literature search was done in Google. Results: The online search identified 190 papers. English abstracts were read and the full papers (or chapters) were retrieved for 90, of which 18 were deemed appropriate. The grey literature search revealed 18 additional papers, and an additional 12 papers were identified from bibliographies of included papers. The common themes identified from the articles became the main consideration for developing an SLS for family practice and include current and past initiatives, system design, incident reporting form and classification system. Conclusion: There is a small but growing body of literature concerning the requirements for developing the reporting component of an SLS for family practice. For the reporting component of an SLS to be successful, there needs to be strong leadership, voluntary reporting, legal protection and feedback to reporters.